THE ROLE OF THE ACMEOLOGIST APPROACH IN THE DEVELOPMENT OF ACMEOLOGICAL MOTIVATION IN FUTURE PHYSICAL EDUCATION TEACHERS - Parmonov Akmal Abdupattayevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
: Interest in this macular axiological approach is associated with the occurrence of changes in the socio-cultural environment. The search for new values in connection with changes in society is of particular importance precisely in the context of the existence of social instability.